Phosphorylation-specific status of RNAi triggers in pharmacokinetic and biodistribution analyses - Trubetskoy, Vladimir S. (Nucleic Acids Res, 2017)
The RNA interference (RNAi)-based therapeutic ARC-520 for chronic hepatitis B virus (HBV) infection consists of a melittin-derived peptide conjugated to N-acetylgalactosamine for hepatocyte targeting and endosomal escape, and cholesterol-conjugated RNAi triggers, which together result in HBV gene silencing. To characterize the kinetics of RNAi trigger delivery and 5΄-phosphorylation of guide strands correlating with gene knockdown, we employed a peptide-nucleic acid (PNA) hybridization assay. A fluorescent sense strand PNA probe binding to RNAi duplex guide strands was coupled with anion exchange high performance liquid chromatography to quantitate guide strands and metabolites. Compared to PCR- or ELISA-based methods, this assay enables separate quantitation of non-phosphorylated full-length guide strands from 5΄-phosphorylated forms that may associate with RNA-induced silencing complexes (RISC). Biodistribution studies in mice indicated that ARC-520 guide strands predominantly accumulated in liver. 5΄-phosphorylation of guide strands was observed within 5 min after ARC-520 injection, and was detected for at least 4 weeks corresponding to the duration of HBV mRNA silencing. Guide strands detected in RISC by AGO2 immuno-isolation represented 16% of total 5΄-phosphorylated guide strands in liver, correlating with a 2.7 log(10) reduction of HBsAg. The PNA method enables pharmacokinetic analysis of RNAi triggers, elucidates potential metabolic processing events and defines pharmacokinetic-pharmacodynamic relationships.